Political competition and convergence to fundamentals : with application to the political business cycle and the size of government - J. Stephen Ferris; Soo-Bin Park; Stanley L. Winer (Center for Economic Studies and ifo Institute (CESifo), 2006)
We address the problem of how to investigate whether economics, or politics, or both, matter in the explanation of public policy. The problem is first posed in a particular context by uncovering a political business cycle (using Canadian data for 130 years) and by taking up the challenge to make this fact meaningful by finding a transmission mechanism through actual public choices. Since the cycle is in real growth, and it is reasonable to suppose that public expenditure would be involved, the central task then is to investigate the role of (partisan and opportunistic) political factors, as opposed to economic fundamentals, in the evolution of government size. We proceed by asking whether the data allow us to distinguish between the convergence and the nonconvergence hypotheses. Convergence means that political competition forces public spending to converge in the long run to a level dictated by endowments, tastes and technology. Nonconvergence is taken to mean that political factors other than the degree of political competition prevent convergence to that long run. The general idea here, one that may be applied in any situation where the key issue is the role of economics versus politics over time, is that an overtly political factor can be said to play a distinct role in the evolution of public choices if it can be shown to lead to departures from a dynamic path defined by the evolution of economic fundamentals in a competitive political system.
Keywords: H1; H3; H5; 330; public expenditure; size of government; long run versus short run; opportunism; partisanship; political competition; cointegration; Öffentliche Ausgaben; Public Choice; Staatsquote; Real Business Cycle; Schätzung; Kanada